Pengaruh Kredit Usaha Rakyat (Kur) TerhadapPerkembangan Usaha Mikro Kecil Dan Menengah (Umkm) Di Kabupaten Mempawah - B01108057, M. ICHFAN FIRDIANSYAH (Jurnal Pembangunan dan Pemerataan, 2015)
The study entitled "The Effect of Credit (KUR) The Development of Micro, Small and Medium Enterprises (SMEs) in the District Mempawah." The purpose of this study was to determine and analyze the impact or influence of lending funds to the development of KUR entrepreneurs business customers Enterprises Kabpaten small Mempawah. The research method is quantitative descriptive analysis tool used is a simple regression analysis. Variable research is the realization of KUR loans as variables that affect (X) and two variables from the customer side of the turnover of sales and use of labor as a variable that is affected (Y1, Y2). The data used is primary data survey conducted in 2014 against 60 respondents BRI Mempawah KUR loan recipients. Also used as a secondary data also support the implementation of the report KUR BRI Mempawah Branch and Regional, Data from BPS. The results showed that the effectÂ  of lending fund (KUR BRI Mempawah) a positive impact on increasing the number of sales turnover with an average increase of Rp2.587.500 or 25.50%, with funds received an average of Rp11,000,000, - Effect on the use of labor is also positive with the addition of an average of one person after the loan. Regression analysis showed that the influence of KUR on sales turnover is positive with a regression coefficient of 0,494 and constants of 8.335. This means that every one amount of KUR funds amounting 4,94 Rupiah effect on sales turnover. While the impacts of the use of labor is also positive with a regression coefficient of 0.981 and constanta of negatif (-12.773). This means that with the gave of fund (KUR/loans) provide an increase of 0.494 or 1 person workforce. The constant negative value means that if there is no (additional) funds KUR the labor used to be reduced. Keywords: People's Business Credit, Small Business, Turnover, Employment.